The Effect of Student’s Intelligence in Writing Narrative Text at Grade X of Sma Methodist Berastagi - Marisa Yunita Br Depari; Liza Sri Devi; Herman; Harpen Silitonga; Lasdamena Siadari (Scholars Digest Publishing, 2022)
This research is aimed to investigate the effectiveness of student’s intelligence in writing narrative in SMA Methodist Berastagi. The type of this study was quantitative. Data were collected by Pre-test and Post-test. The result of the study reveal that: The average score obtained by grade X students at SMA Methodist Berastagi based on The Result Pre-Test in Experimental Group was 57,8, the highest score was 75, and the lowest score was 33. The average score obtained by grade X students at SMA Methodist Berastagi based on The Result of Pre-Test on Control Group was 64,6 the highest score was 75, and the lowest score was 45. The average score obtained by grade X students at SMA Methodist Berastagi based on The Result of Post Test in Experimental Group was 80,1 , the highest score was 94, and the lowest score was 71. The average score obtained by grade X students at SMA Methodist Berastagi based on The Result of Post-Test in Control Group was 79.2, the highest score was 92, and the lowest score was 71. Based on the results of inferential statistical analysis using the t-test formula, it is known that the t-test value is 423, and t-table = 170 is obtained at a significant level of 5%, therefore t-test > t- table at the significance level is 0.05, so the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, which means that there is an influence of linguistic intelligence factors on students' writing skills.
Keywords: Student’s Intelligence, Writing Narrative Text.